A evolução histórica das ações afirmativas e a justificação filosófica da decisão judicial - Pistinizi, Bruno Fraga (2009)
The principle of legal equality has always been studied by philosophers and studious not only related to law, but from other parts of human knowledge. Together with this principle, the inescapable search for justice displayed as main concern from the states around the globe, due to the consequences from the French and American revolutions on the constitutionalists ideals rose from this movement. Created from the institutionalization of the fundamental warranties, it was formally established the equality on the constitutional text at the same time that the conception of the equality principle does not show as an efficient instrument of warranty among political groups that represent the several social segments. Therefore, it began the dissemination of the Idea of material or substantial equality, based on the reduction of disparity on society, avoiding the continuation of the state of inequality. For that it has been trying to find a way to solidify the public or private policies that tend to accomplish the equality of social sectors historically harmed or that were not benefited from a resources, wealth and opportunities distribution. The global transformation scenario brought out a change on the status quo, having the affirmative actions or policies focus on the unbalanced groups. This dissertation bends on dealing with affirmatives actions at the jurisdictional sphere, highlighting the philosophical aspect of the justification from the judicial decision, granted or inhibited from the discrimination validity. The arguments that link the judge s decision posture, declare relevant effectiveness to the institute, which under the Rawls justice theory or the Dworkin s constructive virtue of law, aim the accomplishment of the equality principle